Bobolizan, forests and gender relations in Sabah, Malaysia - Porodong, P. (2001)
The complex web of relations between people and their environment has often been disturbed by development. For the Rungus, this has eliminated the importance of the institution of bobolizan (traditional priestess). Colonial intervention that changed the administrative system has reduced the influence of traditional leaders in social and resource control. One of the major impacts has been the transformation of indigenous property systems from communal property to individual ownership to favor colonial interest. This has affected indigenous capabilities to support community survival, and women's role in management of forests. Traditionally, the forest was used for cultivation, hunting, gathering, and ritual purposes; now it is a cash generator. These changes in belief and property systems and economic necessity have influenced every aspect of indigenous livelihood. This article analyzes the past socio-political power and the present decline of the bobolizan and the impact of Christianity and state forest policies on gender relations among the Rungus of Sabah, Malaysia.